2007
DOI: 10.1016/j.bbamem.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric states of the SecA and SecYEG core components of the bacterial Sec translocon

Abstract: Many proteins synthesized in the cytoplasm ultimately function in non-cytoplasmic locations. In Escherichia coli, the general secretory (Sec) pathway transports the vast majority of these proteins. Two fundamental components of the Sec transport pathway are the SecYEG heterotrimeric complex that forms the channel through the cytoplasmic membrane, and SecA, the ATPase that drives the preprotein to and across the membrane. This review focuses on what is known about the oligomeric states of these core Sec compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 98 publications
1
25
0
Order By: Relevance
“…This finding has been confirmed by thiol-cross-linking (11,12) and by cryoelectron microscopy analysis of the eukaryotic Sec complex bound to a translating ribosome (13). It is thus well-established that a single SecY copy is sufficient to form the translocation pathway, yet it remains mysterious that the channel exists as oligomers (14)(15)(16)(17).…”
mentioning
confidence: 51%
“…This finding has been confirmed by thiol-cross-linking (11,12) and by cryoelectron microscopy analysis of the eukaryotic Sec complex bound to a translating ribosome (13). It is thus well-established that a single SecY copy is sufficient to form the translocation pathway, yet it remains mysterious that the channel exists as oligomers (14)(15)(16)(17).…”
mentioning
confidence: 51%
“…These conformational rearrangements convert SecA from a water-soluble dimeric protein to an integral membrane protein, whose oligomeric state is as yet unclear despite extensive effort. 82 The complex overall architecture of the cytoplasmic form of SecA, which represents the closed form, was first revealed at atomic resolution in a crystal structure of Bacillus subtilis SecA reported by Hunt et al 81 The structure showed the unique multiple domain organization of SecA ( Figure 4A). The motor domains of SecA (termed NBF in the figure) share homology with the super family II DEAD helicases, 83 which bind nucleotide at the interface between the two Using Signal Peptides to Explore Protein Export 313 motor domains.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 92%
“…47). We mapped the 20 SecA residues that were positive for SecY photocross-linking on to front-to-front and back-to-back models of the SecA⅐SecYEG complex that were made in silico (Fig.…”
Section: Resultsmentioning
confidence: 99%